Relationship Between Knowledge Levels And Adolescents' Attitudes About Sex Education - Srinayanti, Yanti; Rahayu, Yuyun; Een, Ayunda (Asy-Syifa : Journal of Science and Technology Nursing, 2024)
Purpose: This study aims to determine the relationship between the level of knowledge and the attitude of adolescents in class VII and VIII MTS Nu Ciamis. Methods: This study used quantitative methods with a cross sectional approach, the sample size was 33 respondents. The sampling method used total sampling technique. The research instrument used a questionnaire that had been tested for validity and reliability with a Cronbach Alpha coefficient value of 0.632. Data were analysed using chi-square. Results: the level of respondents about sex education attitudes in the positive category was 15 people (45.5%), and the negative category was 18 people (54.5%). The data shows that the attitude of students in grades VII and VIII has a negative attitude about sex education. Conclusion: The results of the study with chi square test analysis showed a p-value of 0.283> 0.05, so Ho was accepted and Ha was rejected. These results indicate that there is no relationship between the level of knowledge and attitude.